Pengaruh Kualitas Produk, Harga, Dan Citra Merek Terhadap Keputusan Pembelian Produk Smartphone Merek Samsung (Studi Pada Pengguna Smartphone Samsung di Pesantren Ainul Yaqin Unisma) - Maera Yulia; Rois Arifin; Ita Athia (UNIVERSITAS ISLAM MALANG, 2022)
AbstractThis study was conducted with the following objectives: Determining and analyzing the impact of product quality on Samsung smartphone purchase decisions. Determine and analyze the impact of price on Samsung smartphone purchasing decisions. Determine and analyze the impact of brand image on the decision to purchase a Samsung smartphone. The data used is primary data, which is obtained from questionnaires filled out directly by the respondents. The population that is the object of this research is students who are at the Ainul Yaqin Islamic Boarding School, Malang Islamic University. The sampling technique used in this study used purposive sampling with a total of 90 respondents. Testing the data in this study used the validity test, reliability test, normality test, multiple linear regression test, multicollinearity test, heteroscedasticity test, F test, t test, and coefficient of determination. The results of the data analysis in this study describe the variables of product quality, price, and brand image simultaneously and partially have a significant effect on purchasing decisions for Samsung smartphones. Keywords: Product Quality, Price, Brand Image, And Purchase Decision